Racial change and income tax policy in the US states. (27th August 2021) - O'Brien, Rourke; Travis, Adam
Abstract: This article examines the social correlates of US state income tax policy-making between 1980 and 2008. We focus on the three factors the existing research suggests that are relevant to redistributive policy-making: income structure, left power resources and racial composition. We employ a holistic measure of state income taxation—the dollar-weighted average marginal tax rate—that captures both the overall level of taxation as well as the distribution of tax incidence, key determinants of the redistributive effect of income tax policy. Our analyses examine within-state changes over time as estimated using both actual and fixed income distributions, which enables us to isolate real changes in tax policy from shifts in the income distribution. We find evidence that increases in the percentages of Black and Hispanic residents are associated with a decrease in average marginal tax rate on wage income. We situate these findings within the broader literature on the social determinants of redistributive policy-making.